2023
DOI: 10.1186/s12889-023-15621-y
|View full text |Cite
|
Sign up to set email alerts
|

Low educational attainment is associated with higher all-cause and cardiovascular mortality in the United States adult population

Abstract: Introduction Educational attainment is an important social determinant of health (SDOH) for cardiovascular disease (CVD). However, the association between educational attainment and all-cause and CVD mortality has not been longitudinally evaluated on a population-level in the US, especially in individuals with atherosclerotic cardiovascular disease (ASCVD). In this nationally representative study, we assessed the association between educational attainment and the risk of all-cause and cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Our results were similar to previous studies in Cuba, 10 US 28 and Italy. 29 Stephanie Ross et al. 10 also found that the death risk of population with the lowest education level was 1.79 times that of those with the highest education, and the effect among women was more pronounced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results were similar to previous studies in Cuba, 10 US 28 and Italy. 29 Stephanie Ross et al. 10 also found that the death risk of population with the lowest education level was 1.79 times that of those with the highest education, and the effect among women was more pronounced.…”
Section: Discussionmentioning
confidence: 99%
“…found that compared with individuals not completing primary school, the cancer mortality of those complete university had a HR of 0.57 among men and 0.84 among women. Najah 29 et al. showed compared to population with college and above education, the HR of those who didn't finish high school was 2.03.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that educational attainment is known as one of health’s social determinants, it is important to note how previous studies have linked low educational attainment to the occurrence of diseases [ 46 , 47 ]. Regardless of the acknowledged association between educational attainment and the occurrence of orofacial clefts, the contradiction or variation between research findings does not yet allow a solid conclusion.…”
Section: Reviewmentioning
confidence: 99%
“… 5 Current frameworks to capture SDOH burden are either based on solitary measures of individual SDOH or indices that capture a limited number of social determinants without due attention to the interconnected nature of SDOH across established domains. 6 9 10 In addition, such indices have mostly been developed in subgroups without diabetes or in the general population, 11 and predict non-mortality endpoints. 12 To our knowledge, comprehensive SDOH indices have not been used to capture cumulative social disadvantage and assess mortality risk in adults with diabetes.…”
Section: Introductionmentioning
confidence: 99%